Quarantine and testing strategies in contact tracing for SARS-CoV-2: a modelling study. (March 2021) - Quilty, Billy J; Clifford, Samuel; Hellewell, Joel; Russell, Timothy W; Kucharski, Adam J; Flasche, Stefan; Edmunds, W John; ,; Atkins, Katherine E; Foss, Anna M; Waterlow, Naomi R; Abbas, Kaja; et al.
Summary: Background: In most countries, contacts of confirmed COVID-19 cases are asked to quarantine for 14 days after exposure to limit asymptomatic onward transmission. While theoretically effective, this policy places a substantial social and economic burden on both the individual and wider society, which might result in low adherence and reduced policy effectiveness. We aimed to assess the merit of testing contacts to avert onward transmission and to replace or reduce the length of quarantine for uninfected contacts. Methods: We used an agent-based model to simulate the viral load dynamics of exposed contacts, and their potential for onward transmission in different quarantine and testing strategies. We compared the performance of quarantines of differing durations, testing with either PCR or lateral flow antigen (LFA) tests at the end of quarantine, and daily LFA testing without quarantine, against the current 14-day quarantine strategy. We also investigated the effect of contact tracing delays and adherence to both quarantine and self-isolation on the effectiveness of each strategy. Findings: Assuming moderate levels of adherence to quarantine and self-isolation, self-isolation on symptom onset alone can prevent 35% (95% uncertainty interval [UI] 10–59) of onward transmission potential from secondary cases. 14 days of post-exposure quarantine reduces transmission by 48% (95% UI 18–79). Quarantine with release after a negative PCR test 7 days after exposure might avert a similar proportion (50%, 95% UI 23–80; risk ratio [RR] 1·02, 95% UI 0·88–1·41) to that of the 14-day quarantine period, as would quarantine with a negative LFA test 7 days after exposure (49%, 95% UI 20–78; RR 1·00, 0·82–1·28) or daily LFA testing without quarantine for 5 days after tracing (50%, 95% UI 24–79; RR 1·04, 0·69–1·79) if all tests are returned negative. A stronger effect might be possible if individuals isolate more strictly after a positive test and if contacts can be notified faster. Interpretation: Testing might allow for a substantial reduction in the length of, or replacement of, quarantine in the control of onwards transmission from contacts of SARS-CoV-2-infected individuals. Decreasing test and trace delays and increasing adherence will further increase the effectiveness of these strategies. Further research is required to empirically evaluate the potential costs (increased transmission risk, false reassurance) and benefits (reduction in the burden of quarantine, increased adherence) of such strategies before adoption as policy. Funding: National Institute for Health Research, UK Research and Innovation, Wellcome Trust, EU Horizon 2021, and the Bill & Melinda Gates Foundation.